Characterisation of Tunisian layered clay materials to be used in semisolid health care products. (August 2014) - Mefteh, S.; Khiari, I.; Sanchez-Espejo, R.; Aguzzi, C.; López-Galindo, A.; Jamoussi, F.; Viseras, C.
Abstract : The possibilities of nine Tunisian clay samples to be used in semisolid health care products have been evaluated. Clays from Aleg formation (Conacian–Santonian) at Jebel Romana (R1, R2, R3, R4, R5 and R6) and Jebel Aidoudi (AYD3) and clay potter formation (Pliocene) at Menzel Temime, Cap Bon (CBL) and Jebel Ayat (JAD12) were characterised, including their mineralogical and chemical compositions, textural features and technical properties. Two commercial clay samples were also included as reference materials. Samples from meridional Atlas were mainly composed of smectites, whereas those from septentrional Atlas and Saharian platform were illitic or illitic–smectitic. All samples were very fine powders mainly constituted by irregularly flake shaped particles. By comparison with the commercial materials, those samples with better perspectives in future semisolid formulations were R1–R3, R5 and AYD3. The non-selected samples showed mineral impurities and/or technical features that should require treatments before considering their possible use.